Mechanical Engineering, Industrial Materials and Industrial Technologies : Selected, Peer Reviewed Papers from the 2015 2nd International Conference on Mechanical Engineering, Industrial Materials and Industrial Electronics (MII 2015), March 14-15, 2015, London, UK - Yang, Dehuai (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 2015 2nd International Conference on Mechanical Engineering, Industrial Materials and Industrial Electronics (MII 2015), March 14-15, 2015, London, UK. The 31 papers are grouped as follows: Chapter 1: Properties of Materials, Technologies of Production and Processing; Chapter 2: Design and Research of Machines and Mechanisms, Mechatronics and Control; Chapter 3: Safety and Reliability of Industrial Objects; Chapter 4: Signal and Data Processing, Computer Algorithms.